2021
DOI: 10.3389/fncir.2021.746582
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Mesoprefrontal Dopaminergic System in Health and Disease

Abstract: Midbrain dopaminergic neurons located in the substantia nigra and the ventral tegmental area are the main source of dopamine in the brain. They send out projections to a variety of forebrain structures, including dorsal striatum, nucleus accumbens, and prefrontal cortex (PFC), establishing the nigrostriatal, mesolimbic, and mesoprefrontal pathways, respectively. The dopaminergic input to the PFC is essential for the performance of higher cognitive functions such as working memory, attention, planning, and deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 203 publications
(284 reference statements)
0
16
0
Order By: Relevance
“…The dopamine (DA) system undergoes profound changes across the lifespan, along with concomitant alterations in cognition ( (Bäckman et al, 2010;Islam et al, 2021;Li et al, 2010;Reynolds and Flores, 2021a;Wahlstrom et al, 2010), for reviews). In childhood and adolescence, ongoing maturation of the prefrontal DA system is associated with excessive DA activity (Islam et al, 2021;Reynolds and Flores, 2021a;Wahlstrom et al, 2010Wahlstrom et al, , 2007, constraining the development of executive functions (Diamond, 2009;Diamond et al, 2004;Diamond and Baddeley, 1996;Klune et al, 2021). At older ages, DA losses may result in insufficient DA modulation (Lindenberger et al, 2008;Nagel et al, 2008), and decline in multiple cognitive domains (Bäckman et al, 2000(Bäckman et al, , 2006Karalija et al, 2019;Nyberg et al, 2010;Volkow et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The dopamine (DA) system undergoes profound changes across the lifespan, along with concomitant alterations in cognition ( (Bäckman et al, 2010;Islam et al, 2021;Li et al, 2010;Reynolds and Flores, 2021a;Wahlstrom et al, 2010), for reviews). In childhood and adolescence, ongoing maturation of the prefrontal DA system is associated with excessive DA activity (Islam et al, 2021;Reynolds and Flores, 2021a;Wahlstrom et al, 2010Wahlstrom et al, , 2007, constraining the development of executive functions (Diamond, 2009;Diamond et al, 2004;Diamond and Baddeley, 1996;Klune et al, 2021). At older ages, DA losses may result in insufficient DA modulation (Lindenberger et al, 2008;Nagel et al, 2008), and decline in multiple cognitive domains (Bäckman et al, 2000(Bäckman et al, , 2006Karalija et al, 2019;Nyberg et al, 2010;Volkow et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…DRD2 is a membrane-bound GPCR, and, as mentioned previously, it is known to be exceedingly difficult to study in isolation from its host cell. Further, DRD2 expression levels differ widely according to brain region, layer, and other biochemical variables. Thus, to validate our approach, we first determined whether we could detect the DRD2 expression using our mutant cell line, which exogenously expresses DRD2. We found that DRD2 protein could indeed be detected via mass spectrometry following photo-cross-linking of probe and biotin–streptavidin pulldown.…”
Section: Resultsmentioning
confidence: 99%
“…Higher-order cognitive and executive functions such as working memory and attention rely on activation of mesocortical dopaminergic pathways, particularly towards the DLPFC [ 50 , 51 ], whereas the dopaminergic neurons in the anterior region of the cingulate cortex (BA25) appear to play a causal role in behavioural changes such as emotion, negative affect and anhedonia [ 52 ]. Dysfunction of dopaminergic neurotransmission in these cerebral areas was associated with impaired social and cognitive functions typically seen in neurodevelopmental disorders such as schizophrenia, autism spectrum disorder and ADHD, as well as in depression, impulsivity and substance abuse disorders [ 53 ]. The strong association between total ADD, attention and DRD2 rs4274224 also confirms findings from a previous study investigating the association of this genetic marker with executive functions in an obesity context [ 54 ] and from meta-analyses reporting significant associations between some DRD2 polymorphisms and ADHD [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%